Adverse Childhood Experiences and Intimate Partner Violence Among Sexual Minority Young Adults: The Roles of Alcohol Consequences and Discrimination - Grocott, Lauren R. (Journal of interpersonal violence, 2025)
Adverse childhood experiences (ACEs) are associated with intimate partner violence (IPV) perpetration. A posited mechanism explaining the link between ACEs and IPV is alcohol use consequences. Yet, few studies have examined this relationship among sexual minority young adults or how chronic and unique discrimination due to their marginalized identity (i.e., minority stress) may influence these associations. This study examined whether alcohol use consequences mediated the relationship between ACEs and IPV perpetration, and whether minority stress moderated this mediated relationship. Sexual minority young adults who used alcohol in the past month (N = 344; age 18–25) in a dating relationship completed a survey on ACEs, IPV, alcohol and minority stress. We hypothesized: (a) alcohol use consequences would mediate the association between ACEs and IPV perpetration and (b) higher discrimination would moderate the mediation of alcohol use consequences in the relationship between ACEs and IPV perpetration. ACEs (B = 0.74, p = .010) and alcohol use consequences (B = 0.64, p = .007), were significantly associated with psychological, but not physical, IPV perpetration. Alcohol use consequences did not mediate the association between ACEs and any IPV type. In addition, everyday discrimination was not a significant moderator. ACEs and alcohol use consequences contribute to the risk for IPV perpetration among sexual minority young adults. Future research is needed to determine how alcohol use consequences may impact risk for IPV perpetration among those who have experienced ACEs.